AB0037 Serum cytokine signature in mucocutaneous and ocular behÇet's disease. (15th June 2017) - Lopalco, G; Lucherini, OM; Cantarini, L; Lopalco, A; Venerito, V; Fornaro, M; Natuzzi, D; Galeazzi, M; Lapadula, G; Iannone, F
Abstract : Background: Behçet's disease (BD) is a multi-systemic inflammatory disorder consisting of recurrent oral aphthosis, genital ulcers, and chronic relapsing bilateral uveitis. However, many other organs including the vascular, gastrointestinal, neurological, and musculoskeletal systems can be affected. Pathogenetically, both innate and adaptive immunity have shown to play a pivotal role, and several proinflammatory cytokines derived from Th1 and Th17 lymphocytes seem to be involved in different pathogenic pathways leading to development of the clinical manifestations. Objectives: The primary aim of our study was to compare a core set of proinflammatory cytokines between patients with BD and healthy control (HC). The secondary aim was to evaluate potential correlations between these putative circulating biomarkers, the status of disease activity, and the specific organ involvement at the time of sample collection. Methods: Fifty-four serum samples were collected from 46 BD patients (17 males, 29 females, mean age 45, 5±11, 3 years), and 19 HC (10 males, 9 females, mean age 43±8.3 years). Twenty-five serum cytokines (APRIL/TNFS13, BAFF/TNFSF13B, sCD30/TNFRSF8, sCD163, Chitinase3-like1, gp130/sIL-6Rb, IFNb, sIL-6Ra, IL-10, IL-11, IL-19, IL-20, IL-26, IL-27 (p28), IL-28A/IFN-lambda2, IL-29/IFN-lambda1, IL-32, IL-34, IL-35, LIGHT/TNFSF-14, Pentraxin-3, sTNF-R1, sTNF-R2, TSLP and TWEAK/TNFSF-12) were simultaneously quantified using a Bio-Rad cytokine bead arrays. Results: Serum levels of Chitinase3-like1, gp130/sIL-6Rb, IL-11, IL-26, sTNF-R1, sTNF-R2 were significantly higher in BD patients than in HC. Specifically, serum concentration of sTNF-R1 (p<0.01) and sTNF-R2 (p<0.01) resulted higher in both active- and inactive-BD than HC, whilst Chi-tinase3-like1 (p<0.05) and gp130/sIL-6Rb (p<0.01) serum levels were significantly higher in in-active-BD, and IL-26 (p<0.01) in active-BD than HC. No differences were observed between inactive- and active- BD group. In addition, comparing cytokines levels in patients affected by mucocutenous manifestations with (MO-BD) or without (M-BD) ocular involvement we observed that gp130/sIL-6Rb, sIL-6Ra, IL-35, and TSLP serum levels were significant enhanced in MO-BD compared to M-BD subgroup. Conclusions: Our findings showed a signature of IL-6, TNF-α as well as of Th17 response in BD patients due to increased levels of gp130/sIL-6Rb, sTNF-R1, sTNF-R2, IL-26 respectively. This evidence could contribute to improve the knowledge regarding the role of these citokines in the induction of specific BD clinical features References: Lopalco G, Lucherini OM, Vitale A, Talarico R, Lopalco A, Galeazzi M, et al. Putative Role of Serum Amyloid-A and Proinflammatory Cytokines as Biomarkers for Behcet's Disease. Medicine (Baltimore) (2015) 94(42):e1858. Lucherini OM, Lopalco G, Cantarini L, Vitale A, Rotondo C, Lopalco A, et al. Correlation between serum amyloid-A and serum levels of proinflammatory cytokines in patients with Behçet's disease. Pediatric Rheumatology Online Journal (2015) 13(Suppl 1):P6. Turan B, Pfister K, Diener PA, Hell M, Möller B, Boyvat A, et al. Soluble tumour necrosis factor receptors sTNFR1 and sTNFR2 are produced at sites of inflammation and are markers of arthritis activity in Behçet's disease. Scand J Rheumatol (2008) 37(2):135–41. Disclosure of Interest: None declared